Analysis Of Constraints And Challenges In Optimizing Education And Facillities At The Multatuli Museum - Grace Netania Nauli Panjaitan; Roozana Maria Ritonga (Universitas Pakuan, 2026)
The Multatuli Museum in Rangkasbitung is a historical museum that serves as a means of public education about Eduard Douwes Dekker, anti-colonial thought, and the history of Lebak Regency. In its implementation, the museum still faces various obstacles and challenges in optimizing the quality of education and facilities for visitors. The study, entitled